Metal magnetic powder core ACV iron-silicon optimization production process
By adopting ACV ferrosilicon optimization process in the production process of metal soft magnetic materials, the problem of high frequency loss is solved, and a magnetic powder core with excellent soft magnetic properties is prepared, achieving high efficiency and low loss effect.
Patent Information
- Application Number
- CN202411858050.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-21
AI Technical Summary
Existing metal soft magnetic materials have large losses at high frequencies, which cannot meet the needs of modern high-frequency power electronic products for high efficiency and low loss.
The ACV ferrosilicon production process is optimized, and the fineness ratio of FeSi alloy powder and carbonyl iron powder is used, and the epoxy modified silicone resin is used as the insulating and binder. After suitable pressing and heat treatment, a magnetic powder core with excellent soft magnetic properties is prepared.
It significantly reduces the loss of the magnetic powder core, improves the permeability and saturation magnetization, and meets the requirements of high-efficiency and low-loss for high-frequency power electronic products.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal soft magnetic materials, in particular to an optimized production process of metal magnetic powder core ACV iron silicon. Background Art
[0002] With the development of high-frequency switching power supplies, broadcast satellites, communications, and computer industries, power electronics technology tends to develop with high-frequency and high-current applications as the goal. The increase in frequency and current has led to greater power loss and instability in electronic devices; currently, achieving high power efficiency in power circuits has become a priority, which requires inductors to have larger inductance values and lower power loss.
[0003] Specifically, inductor components are mainly composed of magnetic cores and windings. The magnetic properties and dielectric properties of the magnetic cores; especially the frequency characteristics of the effective magnetic permeability ue and the power loss Pcv, these two properties significantly affect the energy transfer efficiency of the inductor components. Therefore, soft magnetic materials are the key to determining the performance of inductor components. In order to give full play to the potential of high-frequency power electronic products in terms of efficiency, size, weight and power, the magnetic cores for inductors must strike a balance between high saturation magnetization and low core loss characteristics. Traditional soft magnetic materials have significant eddy current effects and high losses at high frequencies; the saturation magnetization of soft ferrites is low and cannot be used as inductor core materials for high current power supplies; it is necessary to improve and optimize its preparation process.
[0004] Based on this, Chinese patent CN101678451B discloses a metal powder for pressed powder magnetic cores and a method for manufacturing pressed powder magnetic cores; it is achieved by heating pure iron powder with a diameter of 10 to 500 μm and a purity of 99 mass % or more to a temperature range of 600°C to 1400°C, and concentrating the Si concentration from the surface of the pure iron powder to a depth of 5 μm through a gas phase reaction within the temperature range, so that the average Si concentration in the depth range is 0.05 mass % to 2 mass %, thereby obtaining a metal powder for pressed powder magnetic cores that improves the adhesion between the insulating material and the particles and improves the electrical insulation without causing a deterioration in compressibility; moreover, the pressed powder magnetic core obtained by this preparation method can have a higher saturation magnetic flux density and low iron loss.
[0005] However, the metal soft magnetic materials disclosed in the prior art still have the technical problem of large high-frequency loss. Specifically, the traditional metal magnetic materials have large high-frequency loss, which is no longer suitable for long-term development in today's environmental protection and resource-saving society. The key to solving this kind of problem is to reduce the loss of the magnetic powder core. For example, we can start from the composition of the material. On the one hand, through the composite effect, different metal magnetic powders are used to prepare the magnetic powder core. On the other hand, according to the principle of close stacking, the density of the magnetic powder core is provided by the particle size ratio. In ferromagnetic materials, the demagnetization field is generally generated by the volume magnetic pole and the surface magnetic pole. The internal demagnetization field is generated by the uneven magnetization near the structural defects and in the porous magnetic powder core material, and the same is true on the surface of the ferromagnetic powder particles. Therefore, by increasing the density of the magnetic powder core, the demagnetization field can be effectively reduced, the magnetic permeability can be increased, and the magnetic core loss of the material can be reduced. In addition, the thermal conductivity of the magnetic powder is low, and the prepared device generates local heat in high-frequency applications, and the heat dissipation function is poor, which is not conducive to the long-term use of the device; therefore, we can start from the coating layer and select a coating material with high thermal conductivity to improve the thermal conductivity of the magnetic powder core, thereby reducing the loss. Summary of the invention
[0006] Based on this, it is necessary to provide an optimized production process for ACV iron silicon of metal magnetic powder core in order to improve the technical problem of high-frequency loss of metal soft magnetic materials.
[0007] An optimized production process of ACV iron silicon metal powder core, calculated by weight, comprises the following steps: S1: First, FeSi alloy powder and carbonyl iron powder are proportioned so that the fineness of the FeSi alloy powder reaches 350 mesh and the fineness of the carbonyl iron powder reaches 150 mesh; and the carbonyl iron powder of 150 mesh accounts for 8wt% to 32wt% of the total mass of the FeSi alloy powder and the carbonyl iron powder, and the two magnetic powders of fineness are stirred and mixed uniformly; S2: dissolving 1 wt % to 3 wt % of epoxy-modified silicone resin and a preset amount of phenolic amine epoxy curing agent in a preset amount of acetone solution, and dissolving by ultrasonication; S3: adding the magnetic powder prepared in step S1 to the solution obtained in step S2, stirring the mixture sufficiently and then drying the mixture; S4: The mixed dry powder is pressed into a ring-shaped product in a preset mold at a preset pressure, and then, under an argon atmosphere, the ring-shaped product is placed in a tube furnace for heat treatment for 2 hours, and the metal magnetic powder core product can be obtained after being taken out.
[0008] Specifically, in step S1, the components of the FeSi alloy powder include, by mass, 6.4 to 6.8 parts of Si, ≤0.03 parts of C, 0.04≤O≤0.06, S≤0.01, P≤0.02, and the remainder is Fe and unavoidable impurities.
[0009] Specifically, in step S1, the components of the carbonyl iron powder include, by mass, N≤0.01 parts, O≤0.7, C≤0.03, and the remainder is Fe and unavoidable impurities.
[0010] Specifically, in step S2, the preparation method of the epoxy-modified silicone resin is: S11: adding a preset amount of epoxy resin 6101 and toluene into a reactor, and dissolving the epoxy resin 6101 in the toluene; S12: The temperature in the reactor is raised to 120° C. to cause reflux, and a preset amount of catalyst is added thereto; S13: adding silicone resin SAR-665 and coupling agent according to a preset ratio; S14: removing water generated by the condensation reaction under reduced pressure; S15: The reaction is carried out at a constant temperature of 120° C. for 4 hours to obtain an epoxy-modified silicone resin.
[0011] Specifically, in step S12, the catalyst is dibutyltin dilaurate.
[0012] Specifically, in step S13, the coupling agent is silane coupling agent KH-550 or KH-560.
[0013] Specifically, in step S1, the added amount of 150 mesh carbonyl iron powder is 25wt% of the total mass of the FeSi alloy powder and the carbonyl iron powder, in parts by mass.
[0014] Specifically, in step S4, the pressure of the pressing molding is 1200 MPa.
[0015] Specifically, in step S4, the annealing temperature is 500°C.
[0016] In summary, the present invention provides an optimized production process for ACV iron-silicon metal magnetic powder core, which firstly proportions FeSi alloy powder and carbonyl iron powder, so that the fineness of the FeSi alloy powder reaches 350 mesh and the fineness of the carbonyl iron powder reaches 150 mesh; and the carbonyl iron powder of 150 mesh accounts for 8wt% to 32wt% of the total mass of the FeSi alloy powder and the carbonyl iron powder, and the two magnetic powders of fineness are stirred and mixed evenly; then 1wt% to 3wt% of epoxy-modified silicone resin and a preset amount of phenolic amine epoxy curing agent are dissolved in a preset amount of acetone solution, and ultrasonically dissolved; then, the prepared magnetic powder and the solution are fully stirred and the mixture is dried; finally, the mixed dry powder is pressed into an annular product in a preset mold at a preset pressure, and then, in an argon atmosphere, the annular product is placed in a tubular furnace for heat treatment for 2 hours, and the metal magnetic powder core product can be obtained after being taken out.
[0017] In the process disclosed by the present invention, carbonyl iron powder with high magnetic permeability, high saturation magnetization and small particle size is used to fill the gaps of FeSi powder with larger fineness, and epoxy modified silicone resin is used as insulation and binder. Finally, under appropriate pressing pressure and annealing temperature, a magnetic powder core with excellent soft magnetic properties can be prepared. Therefore, the ACV iron silicon optimized production process of a metal magnetic powder core of the present invention solves the technical problem of how to improve the high-frequency loss of metal soft magnetic materials. DETAILED DESCRIPTION
[0018] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.
[0019] Specifically, the present invention provides an optimized production process for metal magnetic powder core ACV iron silicon, which comprises the following steps by weight: S1: First, FeSi alloy powder and carbonyl iron powder are proportioned so that the fineness of the FeSi alloy powder reaches 350 mesh and the fineness of the carbonyl iron powder reaches 150 mesh; and the carbonyl iron powder of 150 mesh accounts for 8wt% to 32wt% of the total mass of the FeSi alloy powder and the carbonyl iron powder, and the two magnetic powders of fineness are stirred and mixed uniformly; S2: dissolving 1 wt % to 3 wt % of epoxy-modified silicone resin and a preset amount of phenolic amine epoxy curing agent in a preset amount of acetone solution, and dissolving by ultrasonication; S3: adding the magnetic powder prepared in step S1 to the solution obtained in step S2, stirring the mixture sufficiently and then drying the mixture; S4: The mixed dry powder is pressed into a ring-shaped product in a preset mold at a preset pressure, and then, under an argon atmosphere, the ring-shaped product is placed in a tube furnace for heat treatment for 2 hours, and the metal magnetic powder core product can be obtained after being taken out.
[0020] Specifically, in the aforementioned step S1, the components of the FeSi alloy powder include, by mass, 6.4 to 6.8 parts of Si, ≤0.03 parts of C, 0.04≤O≤0.06, S≤0.01, P≤0.02, and the balance is Fe.
[0021] Specifically, in the aforementioned step S1, the components of the carbonyl iron powder include, by weight: N≤0.01 parts, O≤0.7, C≤0.03, and the balance is Fe.
[0022] Furthermore, in the aforementioned step S2, the preparation method of the epoxy-modified silicone resin is: S11: adding a preset amount of epoxy resin 6101 and toluene into a reactor, and dissolving the epoxy resin 6101 in the toluene; S12: The temperature in the reactor is raised to 120° C. to cause reflux, and a preset amount of catalyst is added thereto; S13: adding silicone resin SAR-665 and coupling agent according to a preset ratio; S14: removing water generated by the condensation reaction under reduced pressure; S15: The reaction is carried out at a constant temperature of 120° C. for 4 hours to obtain an epoxy-modified silicone resin.
[0023] Specifically, in the aforementioned step S12, the catalyst used may be dibutyltin dilaurate, and in the aforementioned step S13, the coupling agent used may be silane coupling agent KH-550 or KH-560.
[0024] In the preparation method of epoxy-modified silicone resin, the feeding ratio of each material is as follows: 55 parts of epoxy resin 6101, 85 parts of toluene, 3 parts of catalyst, 40 parts of silicone resin SAR-665, and 2 parts of coupling agent, calculated by mass.
[0025] Further, the following is an example of feeding several materials in the optimized production process of ACV iron silicon of a metal magnetic powder core of the present invention, calculated by weight: Comparative Example 1: 0 parts of 150-mesh carbonyl iron powder, 100 parts of 350-mesh FeSi alloy powder, 2 parts of epoxy-modified silicone resin, 3 parts of phenolic amine epoxy curing agent and 4 parts of acetone solution.
[0026] Example 1: 8 parts of 150 mesh carbonyl iron powder, 92 parts of 350 mesh FeSi alloy powder, 3 parts of epoxy-modified silicone resin, 4 parts of phenolic amine epoxy curing agent and 5 parts of acetone solution.
[0027] Example 2: 15 parts of 150-mesh carbonyl iron powder, 85 parts of 350-mesh FeSi alloy powder, 3 parts of epoxy-modified silicone resin, 4 parts of phenolic amine epoxy curing agent and 5 parts of acetone solution.
[0028] Example 3: 25 parts of 150 mesh carbonyl iron powder, 75 parts of 350 mesh FeSi alloy powder, 2 parts of epoxy-modified silicone resin, 3 parts of phenolic amine epoxy curing agent and 4 parts of acetone solution.
[0029] Example 4: 32 parts of 150 mesh carbonyl iron powder, 68 parts of 350 mesh FeSi alloy powder, 1 part of epoxy-modified silicone resin, 2 parts of phenolic amine epoxy curing agent and 4 parts of acetone solution.
[0030] Specifically, the selection of magnetic materials and their microstructure have a great influence on the performance of magnetic powder cores. Due to the high saturation magnetization intensity of iron powder, the existing technology mainly uses iron powder as the material of magnetic powder cores. However, pure iron has low resistivity and high loss. In order to reduce the loss, its resistivity needs to be increased.
[0031] Therefore, in the ACV iron-silicon optimized production process of a metal magnetic powder core of the present invention, the resistivity of the magnetic powder core can be improved by introducing the non-metallic element Si to form an F-Si alloy, and the magnetic powder core loss is lower than that of pure iron powder, and it can also have excellent DC bias performance. In addition, compared with flaky and irregular particles, spherical particles have better processing performance. A complete and uniform insulating layer can be formed on the surface of the powder, which is beneficial to improving the resistivity. Furthermore, compared with flaky and irregular particles, spherical particles have better processing performance. A complete and uniform insulating layer can be formed on the surface of the powder, which is beneficial to improving the resistivity. Considering the close relationship between powder particle size and magnetic properties, the present invention can effectively optimize the magnetic properties of the powder by adjusting the bulk density of the powder, the powder particle size distribution and the quality of the binder.
[0032] Specifically, the soft magnetic properties of the aforementioned embodiments are shown in Table 1 below: Table 1: Summary of soft magnetic properties test parameters
[0033] Specifically, the density can be increased by adding an appropriate amount of 150-mesh fine carbonyl iron powder to embed it into the gaps of 350-mesh FeSi coarse powder, thereby obtaining a higher magnetic permeability. After that, as the content of 150-mesh carbonyl iron powder increases, the magnetic permeability and saturation magnetization of the magnetic powder core increase, but if the carbonyl iron powder is added in excess, the filling of the coarse powder gap has reached saturation, and new gaps will form between the fine powders, which will deteriorate the magnetic properties. Therefore, when the addition amount of 150-mesh carbonyl iron powder is 25wt%, the magnetic powder core obtained has the highest magnetic permeability and saturation magnetization.
[0034] Furthermore, when the content of epoxy-modified silicone resin is too low, the magnetic powder coating is incomplete, which is not conducive to suppressing eddy current loss; when the content of epoxy-modified silicone resin is too high, the distance between the magnetic powders increases, which reduces the magnetic permeability. When the resin content is 2wt%, a balance point is reached between the magnetic permeability and the loss, and a higher magnetic permeability is obtained while ensuring lower losses, and the magnetic powder core has the largest quality factor.
[0035] Furthermore, when the pressure is too low during molding, the magnetic powder is not compacted, resulting in a large distance between particles, many gaps inside the magnetic powder core, low magnetic permeability and high loss; when the pressure is too high, the particles are broken, which is not conducive to obtaining excellent magnetic properties. Through the control variable method, the optimal molding process parameters are found to be 1200MPa.
[0036] Furthermore, the internal stress introduced during the molding process will hinder the magnetization process and increase the hysteresis loss, so high-temperature heat treatment is required. The resin is easy to decompose at high temperature, damage the insulation layer, and increase the eddy current loss. Therefore, an appropriate annealing temperature is required. Therefore, the magnetic powder core annealed at 500°C has the highest quality factor and the lowest loss permeability.
[0037] In summary, the present invention provides an optimized production process for ACV iron-silicon metal magnetic powder core, which firstly proportions FeSi alloy powder and carbonyl iron powder, so that the fineness of the FeSi alloy powder reaches 350 mesh and the fineness of the carbonyl iron powder reaches 150 mesh; and the carbonyl iron powder of 150 mesh accounts for 8wt% to 32wt% of the total mass of the FeSi alloy powder and the carbonyl iron powder, and the two magnetic powders of fineness are stirred and mixed evenly; then 1wt% to 3wt% of epoxy-modified silicone resin and a preset amount of phenolic amine epoxy curing agent are dissolved in a preset amount of acetone solution, and ultrasonically dissolved; then, the prepared magnetic powder and the solution are fully stirred and the mixture is dried; finally, the mixed dry powder is pressed into an annular product in a preset mold at a preset pressure, and then, in an argon atmosphere, the annular product is placed in a tubular furnace for heat treatment for 2 hours, and the metal magnetic powder core product can be obtained after being taken out.
[0038] In the process disclosed by the present invention, carbonyl iron powder with high magnetic permeability, high saturation magnetization and small particle size is used to fill the gaps of FeSi powder with larger fineness, and epoxy modified silicone resin is used as insulation and binder. Finally, under appropriate pressing pressure and annealing temperature, a magnetic powder core with excellent soft magnetic properties can be prepared. Therefore, the ACV iron silicon optimized production process of a metal magnetic powder core of the present invention solves the technical problem of how to improve the high-frequency loss of metal soft magnetic materials.
[0039] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0040] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A metal magnetic powder core ACV iron silicon optimization production process, characterized in that: By weight, it comprises the following steps: S1: First, FeSi alloy powder and carbonyl iron powder are proportioned so that the fineness of the FeSi alloy powder reaches 350 mesh and the fineness of the carbonyl iron powder reaches 150 mesh; and the carbonyl iron powder of 150 mesh accounts for 8wt% to 32wt% of the total mass of the FeSi alloy powder and the carbonyl iron powder, and the two magnetic powders of fineness are stirred and mixed uniformly; S2: dissolving 1 wt % to 3 wt % of epoxy-modified silicone resin and a preset amount of phenolic amine epoxy curing agent in a preset amount of acetone solution, and dissolving by ultrasonication; S3: adding the magnetic powder prepared in step S1 to the solution obtained in step S2, stirring the mixture sufficiently and then drying the mixture; S4: The mixed dry powder is pressed into a ring-shaped product in a preset mold at a preset pressure, and then, under an argon atmosphere, the ring-shaped product is placed in a tube furnace for heat treatment for 2 hours, and the metal magnetic powder core product can be obtained after being taken out.
2. The ACV iron-silicon optimized production process of metal magnetic powder core according to claim 1, characterized in that: In step S1, the components of the FeSi alloy powder include, by mass, 6.4 to 6.8 parts of Si, ≤0.03 parts of C, 0.04≤O≤0.06, S≤0.01, P≤0.02, and the remainder is Fe and unavoidable impurities.
3. The ACV iron-silicon optimized production process of metal magnetic powder core according to claim 1 is characterized in that: In step S1, the components of the carbonyl iron powder include, by mass, N≤0.01 parts, O≤0.7, C≤0.03, and the remainder is Fe and unavoidable impurities.
4. The ACV iron-silicon optimized production process of metal magnetic powder core according to claim 1, characterized in that: In step S2, the preparation method of epoxy-modified silicone resin is: S11: adding a preset amount of epoxy resin 6101 and toluene into a reactor, and dissolving the epoxy resin 6101 in the toluene; S12: The temperature in the reactor is raised to 120° C. to cause reflux, and a preset amount of catalyst is added thereto; S13: adding silicone resin SAR-665 and coupling agent according to a preset ratio; S14: removing water generated by the condensation reaction under reduced pressure; S15: The reaction is carried out at a constant temperature of 120° C. for 4 hours to obtain an epoxy-modified silicone resin.
5. The ACV iron-silicon optimized production process of metal magnetic powder core according to claim 4, characterized in that: In step S12, the catalyst is dibutyltin dilaurate.
6. The ACV iron-silicon optimized production process of metal magnetic powder core according to claim 4, characterized in that: In step S13, the coupling agent is silane coupling agent KH-550 or KH-560.
7. The ACV iron-silicon optimized production process of metal magnetic powder core according to claim 1, characterized in that: In step S1, the amount of 150 mesh carbonyl iron powder added is 25wt% of the total mass of the FeSi alloy powder and the carbonyl iron powder, calculated by mass.
8. The ACV iron-silicon optimized production process of metal magnetic powder core according to claim 1, characterized in that: In step S4, the pressure of the press molding is 1200 MPa.
9. The ACV iron-silicon optimized production process of metal magnetic powder core according to claim 1, characterized in that: In step S4, the annealing temperature is 500°C.
Citation Information
Patent Citations
Metallic powder for powder magnetic core and process for producing powder magnetic core
CN101678451B
Soft magnetic composite powder and magnetic powder core preparation method thereof
CN106229104A
Low-loss soft magnetic composite material for high frequency and high power and preparation method thereof
CN115312316A